2020
DOI: 10.3389/fimmu.2020.607175
|View full text |Cite
|
Sign up to set email alerts
|

Mobilized Multipotent Hematopoietic Progenitors Stabilize and Expand Regulatory T Cells to Protect Against Autoimmune Encephalomyelitis

Abstract: Achieving immunoregulation via in vivo expansion of Foxp3+ regulatory CD4+ T cells (Treg) remains challenging. We have shown that mobilization confers to multipotent hematopoietic progenitors (MPPs) the capacity to enhance Treg proliferation. Transcriptomic analysis of Tregs co-cultured with MPPs revealed enhanced expression of genes stabilizing the suppressive function of Tregs as well as the activation of IL-1β–driven pathways. Adoptive transfer of only 25,000 MPPs effectively reduced the development of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…mansoni . MPPs are thought to regulate HSC proliferation in response to inflammation [ 49 ] and play a role in regulation of immune response [ 50 ]. S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mansoni . MPPs are thought to regulate HSC proliferation in response to inflammation [ 49 ] and play a role in regulation of immune response [ 50 ]. S .…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of the relative abundance of different cell types showed significant downregulation of Multipotent Progenitor cells (MPPs) in the children infected with S. mansoni. MPPs are thought to regulate HSC proliferation in response to inflammation [49] and play a role in regulation of immune response [50]. S. mansoni antigens are known to suppress Th1 and Th17 pathways whilst stimulating Th2, B regs and T regs [51].…”
Section: Changes In Cell Type Frequencymentioning
confidence: 99%
“…Further, it was found that HVEM could promote the activation of STAT5, which suggested that HVEM might regulate the induction of Tregs through STAT5/Foxp3 signaling pathway. Foxp3-T cells are found to be the target of IL-1β, which promotes the expression of TGF-β and IL-2-dependent Foxp3 in Treg and ultimately support the expansion of Foxp3+ Treg [33]. Similarly, STAT5 is also found to be a pivotal signaling molecule in the transduction of Tregs [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we assume that the dose of 3.5.10 5 mobMPP represents a relevant ratio for coinjection with 2.10 6 CD3 + T cells containing approximately 1.4 to 1.8.10 5 natural Tregs in mice. Notably, the number of mobMPP required for protection in the allogeneic setting of GVHD is 10 to 30-fold higher than in autoimmune settings where as few as 10,000 and 25,000 mobMPP were sufficient to provide protection against spontaneous type 1 diabetes (7,8) and Experimental Autoimmune Encephalomyelitis (9), respectively. This difference may reflect the multiple target tissues in GVHD where mobMPP may have to migrate to and control the allogeneic response, in contrast with the tissue specificity characterizing the autoimmune experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…We knew also that G-CSF could mobilize murine CD117 + Sca-1 + CD34 + CD11b −/low multipotent progenitor precursor cells (mobMPP), which promoted, in turn, the expansion of regulatory T cells. The latter prevented spontaneous autoimmune type 1 diabetes in the NOD mouse model (7,8) and modulated experimental autoimmune encephalomyelitis (EAE) in the C57BL6/J mouse model (9). These findings prompted us to investigate whether mobMPP could likewise contribute to Treg expansion during allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%